Long term cooling safe shutdown performance analysis for SMART with passive safety system using MARS-KS - Bae, S.H.; Kim, Y.S.; Hoang, N.H.; Sim, S.K. (Nuclear engineering and design, 2022)
•Development of long term cooling safe shutdown analysis methodology using passive safety system.•Long term cooling safe shutdown performance analysis for the SMART reference plant.•Sensitivity analyses of the passive system failures on the long term cooling safe shutdown performance. Passive safety systems have been adopted in reactor design to enhance safety especially in SMRs after the TMI-2 accident in 1979. The passive system has high operational reliability with natural driving forces such as gravity, natural circulation and stored energy. In recent years, development of innovative SMRs has emerged as a global R&D initiative for sustainable energy to challenge the carbon neutrality of climate change. The passive safety system makes reactor design simple and thus enhances the reliability of the reactor. As advanced reactors adopt passive safety systems, regulatory requirements and guides are required. Thus, development of regulatory guide and detailed regulatory review methodology for the passive safety systems is needed. In this paper, long term cooling safe shutdown acceptance criteria and performance analysis methodology are proposed for the regulatory standard design approval for the SMART100 integral reactor with fully passive system which has been jointly developed by KAERI in Korea and K.A.CARE in Saudi Arabia. The long term cooling safe shutdown performance analyses are performed until 72 hours to evaluate the methodology, and sensitivity analyses are also performed to provide a technical basis for the regulatory independent review for the long term cooling performance of the SMART100 passive safety systems.